Comparison of the tolerance of hepatic ischemia/reperfusion injury in living donors: Macrosteatosis versus microsteatosis. Issue 7 (26th May 2014) - Han, Sangbin; Kim, Gaabsoo; Lee, Suk‐Koo; Kwon, Choon Hyuck David; Gwak, Misook; Lee, Sanghoon; Ha, Sangyun; Park, Cheol‐Keun; Ko, Justin Sangwook; Joh, Jaewon
<x xml:space="preserve">Abstract</x> A safe use of intermittent hepatic inflow occlusion (IHIO) has been reported for living donor hepatectomy. However, it remains unclear whether the maneuver is safe in steatotic donors. In addition, the respective importance of macrosteatosis (MaS) and microsteatosis (MiS) is an important issue. Thus, we compared MiS and MaS with respect to the tolerance of hepatic ischemia/reperfusion (IR) injury induced by IHIO. One hundred forty‐four donors who underwent a right hepatectomy were grouped according to the presence of MaS and MiS: a non‐MaS group (n = 68) versus an MaS group (n = 76) and a non‐MiS group (n = 51) versus an MiS group (n = 93). The coefficients of the regression lines between the cumulative IHIO time and the peak postoperative transaminase concentrations were used as surrogate parameters indicating the tolerance of hepatic IR injury. The coefficients were significantly greater for the MaS group versus the non‐MaS group (4.12 ± 0.59 versus 2.22 ± 0.46 for alanine aminotransferase, P = 0.01). Conversely, the MiS and non‐MiS groups were comparable. A subgroup analysis of donors who underwent IHIO for >30 minutes showed that MaS significantly increased the transaminase concentrations, whereas MiS had no impact. Also, IHIO for >30 minutes significantly increased the biliary complication rate for MaS donors (12.1% for ≤ 30 minutes versus 32.6% for >30 minutes, P = 0.04), whereas MiS donors were not affected. In conclusion, the tolerance of hepatic IR injury might differ between MaS livers and MiS livers. It would be rational to assign more clinical importance to MaS versus MiS. We further recommend limiting the cumulative IHIO time to 30 minutes or less for MaS donors undergoing right hepatectomy. Liver Transpl 20:775–783, 2014. © 2014 AASLD.